2022
DOI: 10.3390/molecules27217175
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Anticancer Potential of Polydatin: A Mechanistic Insight

Abstract: Polydatin or 3-O-β-d-resveratrol-glucopyranoside (PD), a stilbenoid component of Polygonum cuspicadum (Polygonaceae), has a variety of biological roles. In traditional Chinese medicine, P. cuspicadum extracts are used for the treatment of infections, inflammation, and cardiovascular disorders. Polydatin possesses a broad range of biological activities including antioxidant, anti-inflammatory, anticancer, and hepatoprotective, neuroprotective, and immunostimulatory effects. Currently, a major proportion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…On the other hand, polydatin, a resveratrol glucoside, has been used for the treatment of various diseases due to its versatile properties, including anti-inflammatory, hypoglycemic, antipyretic, diuretic, expectorant, hypolipidemic, hypouricemic, anticarcinogenic, antioxidant, and anti-atherosclerotic effects [128][129][130][131][132]. Its antioxidant capability is based on the activation of Nrf2, the most important transcription factor against oxidative stress that is also involved in mtUPR [133].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, polydatin, a resveratrol glucoside, has been used for the treatment of various diseases due to its versatile properties, including anti-inflammatory, hypoglycemic, antipyretic, diuretic, expectorant, hypolipidemic, hypouricemic, anticarcinogenic, antioxidant, and anti-atherosclerotic effects [128][129][130][131][132]. Its antioxidant capability is based on the activation of Nrf2, the most important transcription factor against oxidative stress that is also involved in mtUPR [133].…”
Section: Discussionmentioning
confidence: 99%
“…Polydatin represents a natural precursor of resveratrol, in which the hydroxyl is replaced and occupied by a glucopyranoside ring, enabling much better bioavailability than resveratrol, benefiting from the way entering cells via glucose carriers 50 . A number of studies have suggested that polydatin therapeutic effect originates from its anti-inflammatory 51 , antioxidant 52 , and anticancer 53 activities. It remains unclear whether polydatin, like resveratrol, has antioxidation and antitumor properties or constitutes a clinically advantageous approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparative studies of polydatin and resveratrol regarding antioxidative effects in vivo have revealed a better antioxidant activity of polydatin than resveratrol [312,320]. Polydatin has been recognized as a potent anticancer agent, with the ability to regulate various signaling pathways involved in the progression of several kinds of cancers [321,322]. It is mainly involved in cell cycle regulation, apoptosis, autophagy, signaling pathways, EMT, inhibition of inflammation and metastasis, and regulation of enzymes related to oxidative stress [323,324].…”
Section: Polydatinmentioning
confidence: 99%